Estrogen replacement modulates voltage-gated potassium channels in rat presympathetic paraventricular nucleus neurons - Lee, Seul Ki (BioMed Central, 2013)
BACKGROUND: The hypothalamic paraventricular nucleus (PVN) is an important site in the regulation of the autonomic nervous system. Specifically, PVN neurons projecting to the rostral ventrolateral medulla (PVN-RVLM) play a regulatory role in the determination of the sympathetic outflow in the cardiovascular system. In the PVN-RVLM neurons, the estrogen receptor β is expressed. However, to date, the effects of estrogen on PVN-RVLM neurons have not been reported. The present study investigated estrogen-mediated modulation of two voltage-gated potassium channel (Kv) subunits, Kv4.2 and Kv4.3, that are expressed predominantly in PVN neurons and the functional current of Kv4.2 and Kv4.3, the transient outward potassium current (I(A)). RESULTS: Single-cell real-time RT-PCR analysis showed that 17β-estradiol (E2) replacement (once daily for 4 days) selectively down-regulated Kv4.2 mRNA levels in the PVN-RVLM neurons of ovariectomized female rats. There was no change in Kv4.3 levels. Whole-cell patch-clamp recordings demonstrated that E2 also diminished I(A) densities. Interestingly, these effects were most apparent in the dorsal cap parvocellular subdivision of the PVN. E2 also shortened a delay in the excitation of the PVN-RVLM neurons. CONCLUSIONS: These findings demonstrate that E2 exerts an inhibitory effect on the functions of I(A), potentially by selectively down-regulating Kv4.2 but not Kv4.3 in PVN-RVLM neurons distributed in a specific parvocellular subdivision.